Energy Efficient Device-to-Device Weighted Clustering Method in Public Safety Networks - F Rachmawati; I Wahidah; A T Hanuranto; L V Yovita; B Narottama (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2019)
In this work, device-to-device weighted clustering communication is observed in the system of public safety network. Previous algorithm is aimed to avoid unnecessary cluster head re-selection for a steady cluster in the mobile ad-hoc network with a weighted clustering method. Public Safety Network for disaster area, however, differs from the traditional network due to several restrictions, such as shorter end-to-end delay requirement and unavailability of backbone resources. We propose the Improved Weighted Application Clustering Algorithm (IWACA) with additional weight factor for selection of cluster heads in the public safety network. The cluster heads selection algorithm, which is based on the energy-aware of User Equipment (UE) and Quality of Services (QoS), is also taken into consideration and evaluated in the simulation. The results show that energy saving as much as 5.96% can be attained with our proposed algorithm (IWACA) compared to Brust’s. In addition, the delay is decreased 10.96% lower than previous method. With this improvement, the IWACA method becomes more feasible for public safety networks.